The Effect of Problem Based Learning Model on Computational Thinking Ability of Fifth Grade Elementary School Students - Ni Putu Diah Sukma Agustini; Gusti Ngurah Sastra Agustika; Komang Alit Wahyuni (Universitas Pendidikan Ganesha, 2025)
This research was motivated by the low Computational Thinking abilities of elementary school students, particularly in grade V, which have not been optimally facilitated through conventional learning models. The purpose of this study is to describe the effect Computational Thinking of the Problem based learning (PBL) model on students’ Computational Thinking abilities. This study is an experimental research, specifically using a quasi-experimental design. The research design follows the basic pattern of a pre-test post-test non-equivalent control group design. The population in this study consisted of all grade V students from public elementary schools within the same cluster, totaling 15 classes with 417 students. The experimental and control classes were determined using a cluster random sampling technique. The sampling process resulted in two schools being seleComputational Thinking ed as the experimental and control groups. The results of the study showed a significant difference between the experimental and control groups, where students who learned using the PBL model demonstrated a higher improvement in Computational Thinking skills. The implication of this research indicates that the PBL model is effeComputational Thinking ive in fostering 21st-century thinking skills at the elementary school level.